(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper analyses the southwestern script, also known as Tartessian, mainly from a quantitative approach, taking advantage of the structure of this script, which makes it especially suitable for an analysis of this kind. The aim is to assess the discrepancies between researchers in the interpretation of signs without consensus value, where it is possible, with the help of quantitative indicators, but without losing sight of the qualitative in- formation coming from the close relationship between the south-western script and the southeastern Iberian script.